2021
DOI: 10.1021/acsabm.0c01424
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Conjugated Ultrasmall Gold Nanoparticles (2 nm) for Selective Protein Targeting

Abstract: Ultrasmall gold nanoparticles with a metallic core diameter of 2 nm were surface-conjugated with peptides that selectively target epitopes on the surface of the WW domain of the model protein hPin1 (hPin1-WW). The binding to the gold surface was accomplished via the thiol group of a terminal cysteine. The particles were analyzed by NMR spectroscopy, highresolution transmission electron microscopy, and differential centrifugal sedimentation. The surface loading was determined by conjugating a FAMlabeled peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 79 publications
2
28
0
Order By: Relevance
“…62,73,74 This lattice compression of about 0.9% agrees with the literature. 75 The calculated crystallite size (CS = 0.9 ± 0.1 nm) was smaller than the particle size (2 nm by TEM), indicating a polycrystalline (twinned) structure of the nanoparticles in accordance with earlier results on ultrasmall gold nanoparticles, 76 general crystallographic considerations on small nanoparticles, 77 and our TEM analysis given in Figure 1.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…62,73,74 This lattice compression of about 0.9% agrees with the literature. 75 The calculated crystallite size (CS = 0.9 ± 0.1 nm) was smaller than the particle size (2 nm by TEM), indicating a polycrystalline (twinned) structure of the nanoparticles in accordance with earlier results on ultrasmall gold nanoparticles, 76 general crystallographic considerations on small nanoparticles, 77 and our TEM analysis given in Figure 1.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…Rietveld refinement showed that GSH-coated ultrasmall silver nanoparticles had a significantly compressed unit cell ( a = 4.05 ± 0.01 Å) compared to microcrystalline Ag ( a = 4.087 ± 0.001 Å; ICDD #4-0783). ,, This lattice compression of about 0.9% agrees with the literature . The calculated crystallite size (CS = 0.9 ± 0.1 nm) was smaller than the particle size (2 nm by TEM), indicating a polycrystalline (twinned) structure of the nanoparticles in accordance with earlier results on ultrasmall gold nanoparticles, general crystallographic considerations on small nanoparticles, and our TEM analysis given in Figure . The XRD results further demonstrate that the ultrasmall nanoparticles prepared here still have the fcc structure of the bulk silver metal (albeit twinned), unlike atom-sharp clusters. ,,, However, the presence of single-crystalline particles cannot be ruled out, therefore it is possible that the sample contains both single-crystalline and twinned particles.…”
Section: Resultssupporting
confidence: 81%
“…The spectrum of Au-GSH nanoparticles shows broadened, downfield-shifted signals. This NMR peak broadening is a well-known phenomenon that is caused by the presence of a metallic nanoparticle core [ 73 , 74 , 75 , 76 , 77 ]. It depends on the distance between magnetic nucleus and the metal particle.…”
Section: Resultsmentioning
confidence: 99%
“…, biodistribution) can, in principle, be attained through a careful choice of design parameters, such as the particle size, density, and surface chemistry . In addition, usNPs are protein mimics, and usNP–protein interactions exhibit many similarities to a typical biomolecular complexation event. This creates the opportunity to design usNPs having specific interaction modalities with biomolecules, be it through careful control over their sizes, surface chemistries, or both. For example, we have prepared usNPs that selectively target the anion-binding exosites 1 and 2 on the surface of thrombina key enzyme of the coagulation cascadeto allosterically regulate its enzymatic activity. , …”
Section: Introductionmentioning
confidence: 99%